PENGARUH NILAI TUKAR, SUKU BUNGA, INFLASI, GDP DAN CORPORATE TAX RATE TERHADAP STRUKTUR MODAL PERUSAHAAN SEKTOR INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - MUKTI MAHANANI, RAHAYU (Jurnal Ilmu Manajemen (JIM), 2017)
This research aims to determine the effect of Exchange Rates, Interest Rates, Inflation, GDP and corporate tax on corporate capital structure of Infrastructur, Utilities and Transportation Sector Listed on BEI in 2011-2015. This research use Trade off Theory, Signalling Theory and Pecking Order Theory as the basis theory and the sample consisted of 35 companies that were taken using proposive sampling. This research using multiple linear regression model. The results of this research showed that partially variable corporate tax rate has significantly effect on corporate capital structure. The exchange rate and inflation had no effect on corporate capital structure because the company not consider about exchange rate and inflation to determine their capital structure, the company use retained earning or internal fund first instead of using debt in their capital structure. GDP also had no effect on the corporate capital structure because creditor confidence on the grounds that the prospect of the company is no longer seen in terms of debt or profit but from the age of the company that reflect that the company still exists and able to compete. Keywords: Exchange Rates, Inflation, GDP, Corporate Tax Rate, Corporate Capital